You are given the reaction Cu + HNO3 → Cu(NO3)2 + NO + H2O. Half-reactions: First: 3 upper C u right arrow 3 upper C u superscript 2 plus, plus 6 e superscript minus. Second: 2 upper N superscript 5 plus, plus 6 e superscript minus right arrow 2 upper N superscript 2 plus. Complete the final balanced equation based on the half-reactions. Cu + HNO3 Right arrow. Cu(NO3)2 + NO + H2O

Respuesta :

Answer:

Explanation:

You are given the reaction Cu + HNO3 → Cu(NO3)2 + NO + H2O.

Half-reactions:

First: 3 upper C u right arrow 3 upper C u superscript 2 plus, plus 6 e superscript minus. Second: 2 upper N superscript 5 plus, plus 6 e superscript minus right arrow 2 upper N superscript 2 plus.

Complete the final balanced equation based on the half-reactions.

⇒ 3Cu +  

⇒ 8HNO3

⇒ 3Cu(NO3)2 +  

⇒ 2NO +  

⇒ 4H2O

The final balanced equation based on the half-reactions is 3Cu + 8HNO₃ → 3Cu(NO₃)₂ + 2NO + 4H₂O

What is Redox Reaction ?

Redox is a type of chemical reaction in which the oxidation states of substrate change.

Oxidation is the loss of electrons or an increase in the oxidation state of a chemical or atoms within it.

Reduction is the gain of electrons or a decrease in the oxidation state of a chemical or atoms within it

Given Equation ;

Cu + HNO₃ → Cu(NO₃)₂ + NO + H₂O

The first step is to write the oxidation numbers for each atoms in the given equation  

Cu0 + H⁺¹N⁺⁵O⁻²₃ → Cu⁺²(N⁺⁵O⁻²₃)₂ + N⁺²O⁻² + H⁺¹₂O

Identify the oxidizing and reducing agent  

  • OXIDATION ---Cu0 → Cu⁺²(N⁺⁵O⁻²₃)₂ + 2e-    

  • REDUCTION---H⁺¹N⁺⁵O⁻²₃ + 3e- →  N⁺²O⁻²

Balance equation in half reaction  

Cu0 + 2 HNO₃ → Cu⁺²(N⁺⁵O⁻²₃)₂ + 2e-

H⁺¹N⁺⁵O⁻²₃ + 3e- → N⁺²O⁻²

Now balance the charge

Cu0 + 2HNO₃ → Cu⁺²(N⁺⁵O⁻²₃)₂ + 2e- + 2H+

H⁺¹N⁺⁵O⁻²₃ + 3e- + 3H+ → N⁺²O⁻²

Balance the oxygen atom  

Cu0 + 2HNO3 → Cu+2(N+5O-23)2 + 2e- + 2H+

H+1N+5O-23 + 3e- + 3H+ → N+2O-2 + 2H2O

Make electron gain equivalent to electron lost.

3Cu0 + 6HNO3 → 3Cu+2(N+5O-23)2 + 6e- + 6H+

2H+1N+5O-23 + 6e- + 6H+ → 2N+2O-2 + 4H2O

Complete reaction  

3Cu0 + 8H+1N+5O-23 + 6e- + 6H+ → 3Cu+2(N+5O-23)2 + 2N+2O-2 + 6e- + 4H2O + 6H+

Simplify the equation

3Cu0 + 8H+1N+5O-23 → 3Cu+2(N+5O-23)2 + 2N+2O-2 + 4H2O

Final equation  

3Cu + 8HNO₃ → 3Cu(NO₃)₂ + 2NO + 4H₂O

Learn more about Redox Reaction here ;

https://brainly.com/question/13293425

#SPJ2

ACCESS MORE